2023
DOI: 10.1002/jrs.6556
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy investigations of the Martian regolith breccia Northwest Africa 7533: A support to in situ Raman spectroscopy on Mars

Abstract: Using continuous-wave and time-resolved Raman spectroscopy, we investigate and characterize the mineralogy of the NWA 7533 meteorite, a unique Martian regolith breccia. This meteorite is a crucial sample, giving a rare access to the formation and evolution of the primitive Martian crust, with crystallization processes beginning up to $4.4 Ga years ago. We provide an overview of Raman spectra for feldspar, plagioclase, pyroxene, olivine, apatite, merrillite, zircon, pyrite, and various Fe-Cr-Ti oxides like magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…Apatite is a calcium phosphate with the theoretical formula (OH, Cl, F)Ca 5 (PO 4 ) 3 (hydroxyl, chloro-and fluoroapatites, respectively). It is a common mineral in terrestrial rocks and meteorites and was previously identified on Mars 67,68 and is ubiquitous in Martian meteorites 69,70 . Apatites can be magmatic, sedimentary or biological and can trace fluid-rock interactions, giving them particular interest in the context of planetary exploration 37 .…”
Section: The Targetmentioning
confidence: 99%
“…Apatite is a calcium phosphate with the theoretical formula (OH, Cl, F)Ca 5 (PO 4 ) 3 (hydroxyl, chloro-and fluoroapatites, respectively). It is a common mineral in terrestrial rocks and meteorites and was previously identified on Mars 67,68 and is ubiquitous in Martian meteorites 69,70 . Apatites can be magmatic, sedimentary or biological and can trace fluid-rock interactions, giving them particular interest in the context of planetary exploration 37 .…”
Section: The Targetmentioning
confidence: 99%